Çevresel maliyetlerin değişiminde teknolojik gelişmelerin rolü: bir uygulama örneği - Ay, Zafer (My University, 2019)
In this study, in the Marmara Region in a manufacturing company in chemica lindustry which is located among the top 50 companies in the Istanbul Chamber of Industry 500 list were investigated the effects of technological developments on environmental costs. The interview method technique was used to obtain environmental informations from authorized people are working in the environment, project and accounting units of the company were evaluated with in the framework of trend analysis method from financial analysis technigues. It has been determined that the production business units in which the enterprise operates in the change of environmental costs are realized by making various technological investments and increasing the capacity ratios. Some of the technological investments made by the company have been effective in reducing the environmental costs and increased the efficiency rate. Some technological investments, it has caused the environmental costs to increase and at the same time, it has ensured it continues its activities without harming the environment. The relationship between the environmental costs and the financial statements was examined, net results could not be revealed the changes in the balance sheet and income statement items are related to the accounts used in the accounting of the environmental costs were compared investments and environmental costs made by applied enterprise are not completely shared however, as a result of the fac tthat the investments made by the operating company and the environmental costs were not fully shared, although not to a large extent, the existence of a partial relationship has been observed. Due to the presence of concept of social responsibility and full explanation concept, it will be possible to demonstrate the changes in the environmental costs in technology investments as a result of monitoring of environmental costs in financial reports or sharing the environmental costs.

Çalışmada Marmara Bölgesinde kimya sektöründe faaliyet gösteren İstanbul Sanayi Odası (İSO) 500 listesinde ilk 50 şirket arasında yer alan bir üretim işletmesinde teknolojik gelişmelerin çevresel maliyetlere etkisi incelenmiştir. Görüşme yöntemi tekniği kullanılarak işletmenin çevre, proje ve muhasebe birimlerinde çalışan yetkili kişilerden alınan çevresel veriler finansal analiz tekniklerinden trend analiz yöntemi çerçevesinde değerlendirilmiştir. İşletmenin faaliyet gösterdiği üretim iş birimlerine çeşitli teknolojik yatırımlar gerçekleştirmesi sonucu ve üretim kapasitesine bağlı olarak çevresel maliyetlerde değişim tespit edilmiştir. İşletmenin yaptığı bazı teknolojik yatırımlar çevresel maliyetlerini azaltmasında etkili olup verimlilik oranını arttırmıştır. Bazı teknolojik yatırımlar sonucu ise çevresel maliyetlerinin artmasına neden olup, aynı zamanda çevreye zarar vermeden faaliyetlerini sürdürmesini sağlamıştır. Çevresel maliyetler ile mali tablolar arasındaki ilişki incelenmiş, çevresel maliyetlerin muhasebeleştirilmesinde kullanılan hesaplarla ilişkili olan bilanço ve gelir tablosu kalemlerindeki değişimler karşılaştırıldığında uygulama yapılan işletme tarafından yapılan yatırımların ve çevresel maliyetlerin bütünüyle paylaşılmaması sonucu net sonuçlar ortaya konamamış, büyük oranda olmasa da kısmen ilişkinin varlığı gözlemlenmiştir. Sosyal sorumluluk kavramı ve tam açıklama kavramı gereği çevresel maliyetlerin finansal raporlarda izlenmesi veya çevresel maliyetleri paylaşmaları sonucu, çevresel maliyetlerin teknoloji yatırımları karşısındaki değişimi ortaya koymak mümkün olacaktır.
Keywords: Çevre; Çevre ekonomisi; Çevre koruma; Çevre Muhasebesi; Çevre politikası; Çevresel Maliyetler; Çevresel yönleri; Economic aspects; Economic Development; Ekonomik yönleri; Environmental Accounting; Environmental aspects; Environmental economics; Environmental policy; Environmental protection; EnvironmentalCosts; Technological innovations; Technology; Teknoloji Environment; Teknolojik yenilikler